Dental caries and treatment needs of children (6-10 years) in rural Udaipur, Rajasthan - Dhar Vineet; Bhatnagar Maheep (Wolters Kluwer Medknow Publications, 2009)
Objective : This study was done to examine caries prevalence and corresponding treatment needs in school children of rural areas of Udaipur, Rajasthan. Materials and Methods : A total of 750 children of rural areas in the age group of 6-10 years were examined, using WHO index, to record the prevalence of dental caries and treatment needs. The results were subjected to statistical analysis using chi square test. Results : Dental caries was found in 63.20% children, and 85.07% children needed dental treatment. The highest need was of one surface filling (85.73%) followed by sealant (51.20%). Conclusion : Dental caries showed to be a significant health issue in the rural population requiring immediate attention.